Can mortality rates for patients who die within the emergency department, within 30 days of discharge from the emergency department, or within 30 days of admission from the emergency department be easily measured?. Issue 8 (20th July 2006) - Baker, M; Clancy, M
Abstract : Objectives: Death rates are an outcome that can be used to describe a service. We measured three death rates that can be used to describe an emergency department (ED): death rates for those seen in the ED and discharged, those that die within the ED, and those that die after admission. We also wanted to establish how easy it was to obtain these rates and how frequently autopsy was performed. Setting: ED within a large teaching hospital. Results: Between 1 December 2003 and 1 December 2004, 76 060 patients attended the ED of which 205 died within the department. A total of 16 489 were admitted of which 876 died within 30 days. A total of 59 366 were discharged home of which 111 subsequently died over the next 30 days. The rates were 0.19% (111/59 366) for those discharged, 4.6% (766/16 489) for those admitted, and 0.27% (205/76 060) for those patients attending the ED who died within it. The autopsy rate was low (20%) and was more likely if the patient died in the department, died within the first few days of admission, or was young. The data were easy to collect. Conclusions: These three death rates were easy to calculate and could be used to describe the outcome of an ED service. Further research to establish the range of rates for different departments is now required to determine their potential use.